Reg3g overexpression promotes β cell regeneration and induces immune tolerance in nonobese-diabetic mouse model. Issue 6 (14th December 2015) - Xia, Fei; Cao, Hui; Du, Jiao; Liu, Xiulan; Liu, Yang; Xiang, Ming
Abstract : Reg3g-Lv treatment directly increased β cell regeneration and prevented T1D by attenuating autoimmunity. Abstract: The regenerating islet-derived gene was first isolated in regenerated pancreas tissues, greatly contributing to β cell regeneration. It is an anti-inflammatory in response to cellular stress. This encouraged us to investigate the exact role of a novel member of Reg family, regenerating islet-derived gene γ, in type 1 diabetes of nonobese-diabetic mice. For this, Reg3g gene was overexpressed in pancreatic islets, and conferred beneficial effects on β cell regeneration through activating the Janus kinase 2/signal transducer and activator of transcription 3/nuclear factor κB signaling pathway. Lentiviral vector-encoding regenerating islet-derived gene γ treatment also decreased lymphocyte infiltrates of the intra-islet and peri-islet by inducing both differentiation of regulatory T cell and immature dendritic cells of tolerogenic properties, which attenuated autoimmunity. This treatment further contributed to rebalanced levels of type 1/2 helper T cell cytokines and elevated α1-antitrypsin levels in the serum. These results were not observed in phosphate-buffered saline-treated mice or in lentivirus-control mice. We have shown, for the first time, to our knowledge, that regenerating islet-derived gene γ promotes β cell regeneration and preserves β cells from autoimmunity damage by increasing regulatory T cell differentiation and inducing tolerated dendritic cells. This regenerating islet-derived gene γ infusion could probably be developed into an optimal gene therapy for the prevention and reversal of type 1 diabetes.